The Analysis of Current Variations on Mechanical Properties and Microstructure of ASS 316L Welded Joints by TIG Welding - Riswanda; Wahyudin, Faris Khoiri; Azmy, Ilham; Mulyana, Deni; Saragih, Albert Daniel (Program Studi Teknik Mesin Universitas Pamulang, 2025)
Stainless steel 316L pipe welding joints are widely used in industry, especially in the Bio-Medical field. In order to develop research on this field, the Gas Tungsten Arc Welding (GTAW) process was carried out on the butt joint of ASS 316L. In this study, the ASS 316L pipe of 89 mm (3.5 inches), a thickness of 2.6 mm, and a length of 100 mm was investigated. The effect of current variations of 30, 40, and 50A with shielding gas and Argon backing gas were analyzed. ER316L have been selected as filler metal for GTAW process. The results of microstructural observations for all currents showed the formation of dendritic and widmanstanten structures in the weld metal and austenitic phases in the base metal. The mechanical tests has been conducted to find out the ultimate tensile strength and and hardness as well as observations of the macro structure in the weld metal (WM), heat affected zone (HAZ), and base metal (BM) areas. Visual observation of the 40A current showed more stable surface and penetration results compared to the 30 and 50A currents. Observations of the macro structure were correlated with the results of visual observations of the 40A current, indicating good fusion and no defects exceeding the standard. The highest tensile strength test results were obtained in specimens with a current of 50A of 659 MPa, followed by a current of 40A of 651 MPa, and a current of 30A of 649.3 MPa. However, the highest elongation was found in specimens with a current of 40A, which was 45.3%, while specimens with currents of 30A and 50A had the same elongation value of 39.3%. The general distribution of hardness in the weld metal area was greater than in the heat affected zone and base metal areas.